2004
DOI: 10.1038/oby.2004.143
|View full text |Cite
|
Sign up to set email alerts
|

Adult Obesity and the Burden of Disability throughout Life

Abstract: Original participants and at 20 years of follow-up for 2268 Offspring participants. We measured the odds of disability in the Original cohort after 46 years follow-up, and we estimated life expectancy with and without disability from age 50. Two disability measures were used, one representing limitations with mobility only and the second representing limitations with activities of daily living (ADL). Results: Obesity at ages 30 to 49 years was associated with a 2.01-fold increase in the odds of ADL limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 32 publications
2
77
2
6
Order By: Relevance
“…Noteworthy, a 6-y lesser life expectancy in obese subjects aged 30-49 y has been observed 87 as well as a reduction of life expectancy free of disability compared with normal-weight subjects. 88 Thus, these findings suggest that the increased prevalence of obesity in middle-age as in older age may counteract the expected increase of life expectancy of normal-weight subjects.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 78%
“…Noteworthy, a 6-y lesser life expectancy in obese subjects aged 30-49 y has been observed 87 as well as a reduction of life expectancy free of disability compared with normal-weight subjects. 88 Thus, these findings suggest that the increased prevalence of obesity in middle-age as in older age may counteract the expected increase of life expectancy of normal-weight subjects.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 78%
“…The onset of obesity in young and middle adulthood may result in lower physical activity contributing to decreased muscle strength and cardiovascular fitness and greater declines in physical performance because of longer duration of excess body weight and earlier onset of chronic disease. Peeters et al 27 found that obesity at ages 30-49 was associated with 5-6 fewer years free of limitations in ADLs after age 50 compared to those who were normal weight. In the ARIC study, participants who were obese at age 25 had approximately a twofold or higher prevalence of limitations in self-reported physical function and ADLs at ages 52-75.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the higher proportion of smokers in the normal weight group who are at a greater risk of disability, and highlights the need to stratify by smoking status when assessing BMI as a risk factor for ill health. 7,14 The moderating effect of smoking was not evident in females, likely due to the lower prevalence of smoking among females.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such cohorts need comprehensive measures of disability and to have evaluated possible confounders and effect modifiers. Although several studies have analysed the relationship between mid-life BMI and disability, [10][11][12][13][14] data of this kind are lacking. With the prevalence of overweight and obesity increasing across all age groups, it is important to know to what extent excess weight prior to old age is associated with disability in old age.…”
Section: Introductionmentioning
confidence: 99%